The Origin of Free Will in Clement of Alexandria - Nilsen, Fredrik (Nordlit, 2025)
In her latest work, The Life of the Mind, Hannah Arendt claims that Augustine must be considered “the first philosopher of free will”. In my doctoral dissertation, I argued that Arendt was largely right in her claim, although there are also, as Michael Frede has demonstrated, traces of a conception of free will in Epictetus. In this article, however, I argue that Arendt’s claim is wrong, as we already find a concept of free will in Clemens of Alexandria. Clemens uses Aristotle’s term “prohairesis” in a non-Aristotelian way, which lays the foundation for the first conception of free will in the history of philosophy; where Aristotle advocates that the “weak character”, who is characterized by acting in line with desire and against reason, also acts against the decision (prohairesis), Clemens rather takes as a starting point that such a choice is precisely made by the decision (prohairesis). Given that this interpretation is correct and right to describe the Athens-born Clemens of Alexandria as a non-Western philosopher, we must therefore leave the history of Western philosophy behind to find the origin of one of history’s most important and most debated concepts, namely “free will”.